Eroticism in Fr. Franciszek Sawicki’s philosophy of love - Jarosław Babiński (Warszawskie Studia Teologiczne)
Father Franciszek Sawicki is considered to be one of the most important philosophers of the interwar period in Poland. The problem of love must be regarded as one of the most significant among many issues he focused on in his research. Sawicki, one of the precursors of personalistic thinking, understands the essence of love as it functions in a personal relationship. Above all, we should distinguish two areas for the realisation of love: love in relation to God and love in relation to another human being. In both instances, Sawicki emphasises the need to take into account the "erotic moment" for the sake of full and proper understanding thereof. The erotic moment elucidates love as a force that engages not only the emotional and volitional spheres, but also the categorical and existential ones. This approach enables us to appreciate the full dimension of human sexuality as it pertains to the human being and ameliorate the tendency to depreciate or idolise it.